6‐n‐propylthiouracil taste disruption and TAS2R38 nontasting form in Parkinson's disease. Issue 8 (24th March 2018) - Cossu, Giovanni; Melis, Melania; Sarchioto, Marianna; Melis, Marta; Melis, Maurizio; Morelli, Micaela; Tomassini Barbarossa, Iole
ABSTRACT: Background: The few studies that evaluated taste function in Parkinson's disease (PD) showed inconsistent results. The inherited ability to taste the bitter compound of 6‐ n ‐propylthiouracil has been considered to be a paradigm of general taste perception. 6‐ n ‐propylthiouracil taste perception is mediated by the TAS2R38 receptor, and reduced 6‐ n ‐propylthiouracil sensitivity has been associated with several diseases not typically related to taste function. Objectives: We evaluated the 6‐ n ‐propylthiouracil taste perception and the TAS2R38 gene as genetic risk factors for the development of idiopathic PD in PD patients and healthy controls (HC). Methods: The 6‐ n ‐propylthiouracil taste perception was assessed by testing the responsiveness, and the ability to recognize, 6‐ n ‐propylthiouracil and sodium chloride. The participants were classified for 6‐ n ‐propylthiouracil taster status and genotyped for the TAS2R38 gene. Results: A significant increase in the frequency of participants classified as 6‐ n ‐propylthiouracil nontasters and a reduced ability to recognize bitter taste quality of 6‐ n ‐propylthiouracil were found in PD patients when compared with healthy controls. The results also showed that only 5% of PD patients had the homozygous genotype for the dominant tasting variant of TAS2R38, whereas most of them carried the recessive nontaster form and a high number had a rare variant. Conclusions: Our results show that 6‐ n ‐propylthiouracil taster status and TAS2R38 locus are associated with PD. The 6‐ n ‐propylthiouracil test may therefore represent a novel, simple way to identify increased vulnerability to PD. Moreover, the presence of the nontasting form of TAS2R38 in PD may further substantiate that disease‐associated taste disruption may represent a risk factor associated with the disease. © 2018 International Parkinson and Movement Disorder Society